High-frequency transformer isolated AC-DC converter for resilient low voltage DC residential grids - Santos, Nelson (2021)
In a global and growing society, it is necessary to rethink strategies in order to minimize the environmental impact resulting from the progressive increase of energy consumption and the misuse of energy resources. Energy power system converters must be considered as a global way to spare most of the wasted energy. Today, in the power distribution infrastructure, including modern residential buildings, most equipment have power supplies with imbedded AC-DC power converters which may have overall losses as high as 25% regarding the equipment output. Therefore, common DC buses for residential applications are being studied to increase equipment efficiency. This paper presents and designs an AC-DC isolated converter that uses a full-bridge matrix topology with high-frequency isolation transformer and non-electrolytic capacitors to integrate into the future residential buildings DC bus, presenting a reliable alternative to AC power. Non-linear control techniques (sliding mode control and backstepping control) are employed to guarantee stability and disturbance robustness to the output DC low voltage, while enforcing sinusoidal input AC current and power factor correction. Control strategies are described and simulation results are presented and discussed.